Figurative Language in Justin Bieber’s Song Lyrics from Purpose Album - Sudarmini, Ni Kadek Ayu; Santika, I Dewa Ayu Devi Maharani; Pratiwi, Desak Putu Eka (Journal of Language and Applied Linguistics, 2023)
Figurative language is way communication to convey the speaker’s through with meaningful sentences. The purpose of this study is to find the type of figurative language contained in the lyrics of Justin Bieber's song from Purpose Album. In analyzing the data qualitative and descriptive methods are used. The theory used in this research is Knickerbocker and Reninger (1963) to analyze the types of figurative language. According to him there are ten types of figurative language such as: simile, personification, metaphor, synecdoche, allusion, dead metaphor, metonymy, hyperbole, paradox, and the last is irony. From the ten types of figurative language, there are six types found in Justin Bieber's songs in Purpose Album, there are: simile, metaphor, personification, hyperbole, synecdoche, and metonymy. The most type used in this research is simile and hyperbole.